ความตรงของแบบวัดชุดความคิด - Silpakit, Chatchawan; Silpakit, Orawan; Chomchuen, Rossukon (วารสารสุขภาพจิตแห่งประเทศไทย, 2015)
Objective To develop the mindset assessment scale and evaluate the content validity. Materials and methods Item generation was done by document review and content validity study was confirm by expert’s opinion using the Delphi technique and then the questionnaire was applied in 100 persons for internal consistency study by Cronbach’s alpha if item deleted and corrected item total correlation (CITC). Results The 16-item questionnaire was reviewed by 7 experts and 10 items were retained. The 10-item questionnaire was confirmed by 5 experts but the other 2 had further reviewed and finally reconfirmed. The 10- item mindset questionnaire was a 1-6 rating scale (strongly disagree to strongly agree) which composed 4 items of growth mindset and 6 items for fixed mindset. The questionnaire was then tested in 100 persons, most were female (52%) and had the education levels at the bachelor and master degree (74%). The internal consistency, Cronbach’s alpha, was 0.67 and CITCs were ranged between 0.13-0.49. Any item deletion did not yield an increase in Cronbach’s alpha. Conclusion The 10-item mindset assessment scale had the face validity and content validity which could be used for further validity study.